MEDIA PETA KONSEP MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD ISLAM PERTIWI NUSANTARA MAKASSAR - Sumarnianti Usman; Arsad Bahri; Evi Ristiana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study was to determine the influence of mind mapping on students’ learning outcomes. This study was conducted at SD Islam Pertiwi Nusantara, Makassar. The approach of this study was quantitative with quasi-experimental research. The sampling technique was simple random sampling. Then, data were collected through tests, questionnaires, and observations. After that, the data were analyzed by using one-way covariate analysis (ANACOVA), in which the prerequisites, suh as normality, and homogeneity, had been previously tested. The results of this study indicated that mind mapping influenced the students’ learning outcomes and the results of ANACOVA was sig. 0.045 which means Sig. < 0.05.